Investigation on the robust adsorption mechanism of alkyl-functional boric acid nanoparticles as high performance green lubricant additives. (May 2021) - Wu, Hongxing; Yin, Shaochong; Wang, Liping; Du, Yin; Yang, Yong; Shi, Junqin; Wang, Haifeng
Abstract: Layered boric acid (BA) nanoparticle was considered as a promising 'green' lubricant additive due to its bio-degradable. However, its unclear lubrication mechanism and poor dispersion stability cause serious concerns for practical applications. Here, highly oil-dispersed alkyl-functionalized BA nanoparticles with size of about 100 nm were fabricated using a scalable strategy. The friction coefficient reached to around 0.11 with the addition of BA nanoparticles, about 30% lower than that of base oil (0.16). Tribological tests show that the wear reduction reached 40%, and the scuffing load capacity was improved by about 3 times. Lubrication mechanism investigation by molecular dynamics (MD) simulation shows that BA molecules preferentially adsorbed on the friction interface through hydrogen bond. A compact net-like adsorption layer from the decomposed nanoparticles, as well as boron-containing tribofilm, was formed on the rubbing surface to enhance lubrication performance. These solid evidences make BA nanoparticle to be a very promising candidate in practical applications as high performance green additive. Graphical abstract: Image 1 Highlights: MD simulation demonstrates the key role of hydrogen bond at friction interface. Boric acid (BA) molecule preferentially adsorbed on the sliding surface. Alkyl-functionalized BA nanoparticles were fabricated using a simple strategy. The oil suspension with BA nanoparticles remains stable for more than 2 months. Scuffing load capacity was improved by 3 times with the addition of BA nanoparticles.